Performance of RC Beams Strengthened in Flexure and Shear with CFRP and GFRP - Sengun, Kadir; Arslan, Guray (SPRINGER INT PUBL AG, 2024)
An experimental study was carried out on nine reinforced concrete beams with insufficient shear strength to evaluate the shear behavior and performance of beams. One of the beams was not strengthened and designated as the reference beam. Six of them were strengthened in both flexure and shear using two types of composite materials-carbon and glass fiber-reinforced polymer (CFRP and GFRP). Two of them were strengthened with U-wrapped and side-bonded CFRP in only shear. The experimental parameters involve the type of FRP, the number of FRP layers, the clear distance between two adjacent FRP shear strips and the strengthening configuration (completely wrapped, U wrapped and side bonded). The experimental results revealed that (i) applying the FRP sheets for strengthening improved the load carrying and deflection capacities of the tested beams by an average of 143% and 170%, respectively, (ii) strengthening with two layers of CFRP shear strips could transform the failure mode from shear to more ductile flexural failure, (iii) the load-carrying capacity of GFRP-strengthened beams was on the average 34% less than the capacities of those strengthened with CFRP and (iv) using additional CFRP layers for shear strengthening did not provide a proportional increase in strength. The experimental FRP contribution to the shear strength was estimated using equations proposed by various codes and researchers, and the prediction accuracy of the equations was evaluated statistically.
Keywords: Carbon fiber-reinforced polymer (CFRP); Reinforced concrete beams; Glass fiber-reinforced polymer (GFRP); Shear strength; Rectangular beams; Strengthening; REINFORCED-CONCRETE BEAMS; TRANSVERSE STEEL; T-BEAMS; FRP SHEETS; CAPACITY; BEHAVIOR; DESIGN; STRAIN; STRIPS; MODEL; Engineering